2007
DOI: 10.1152/jn.00024.2007
|View full text |Cite
|
Sign up to set email alerts
|

Object Category Structure in Response Patterns of Neuronal Population in Monkey Inferior Temporal Cortex

Abstract: Our mental representation of object categories is hierarchically organized, and our rapid and seemingly effortless categorization ability is crucial for our daily behavior. Here, we examine responses of a large number (>600) of neurons in monkey inferior temporal (IT) cortex with a large number (>1,000) of natural and artificial object images. During the recordings, the monkeys performed a passive fixation task. We found that the categorical structure of objects is represented by the pattern of activity distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
512
8
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(565 citation statements)
references
References 63 publications
34
512
8
1
Order By: Relevance
“…In a recent study in which monkeys were shown images of objects from many natural categories, the population of IT neurons was highly selective for category membership, especially for animate objects like faces and bodies 48 . More indirect evidence for category selectivity is the observation that single IT neurons are more selective for shape features that are useful for object categorization ('non-accidental properties') than for other shape features ('metric properties') 49 .…”
Section: Monkey Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study in which monkeys were shown images of objects from many natural categories, the population of IT neurons was highly selective for category membership, especially for animate objects like faces and bodies 48 . More indirect evidence for category selectivity is the observation that single IT neurons are more selective for shape features that are useful for object categorization ('non-accidental properties') than for other shape features ('metric properties') 49 .…”
Section: Monkey Studiesmentioning
confidence: 99%
“…Computational evidence has also revealed that image fragments of intermediate complexity are more informative for object categorization than fragments of low or high complexity 118,119 , suggesting that neural coding in object-selective areas might be based on such intermediate-complexity shape features. However, a computational description of cortical organization in the ventral pathway remains a distant goal, because current neurophysiologically plausible models cannot yet predict the strong category selectivity that exists in the object-vision pathway 48,120 : for example, the dominance of object category in the selectivities of monkey IT neurons is not predicted by 'standard' hierarchical models 48 . Similar discrepancies might exist in the human brain 100 .…”
Section: Object Category As a Basic Propertymentioning
confidence: 99%
“…Tsunoda et al [54] presented another example where concept hierarchies may play a crucial role (cf., also [53,27]). In combined optical and single unit recordings from inferotemporal cortex of Macaques they found that visual objects evoke blobs of activity in the optical recordings that stay roughly constant in cortical location and size if complex stimuli get successively simplified.…”
Section: Discussionmentioning
confidence: 88%
“…Strong experimental evidence has been provided to support this view [27,43,53,54] up to the highest cognitive levels in human [44,42]. Similarly, many scientists considered feedback processes, often interpreted as top-down attention [26,47,49] or more recently the action of some generative models that aim to reconstruct or predict the input [12,46].…”
Section: Discussionmentioning
confidence: 99%
“…In detail, the "distance" between two stimuli is defined by a measure of dissimilarity between two elicited activity patterns, which can be assessed in a variety of ways, including correlation or rank-correlation analysis, Euclidean and Manhattan distance measure, etc. A widely used measure of dissimilarity is correlation distance, i.e., one minus the correlation between patterns [21].…”
Section: Representing Dissimilarity Structure Of Response Patterns Tomentioning
confidence: 99%